ANALYZING CHANGE MANAGEMENT IN ORGANIZATION - Yonardy, Charles; Mekel, Peggy A. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Every company will be faced a change either business or non-business company. A change will be happened because of technological change, industry change, and institutional rules change. If the company lack in adapt the changing of competition, business cycles, technology and institutional rules the company might face a bankruptcy. Why? To make a successful change there are steps and process of change. Research objectives are to analyze what should company do in order to do change management and to analyze the change management inside organizational to help manager or owner reach their business goal in organizational. This type of research is qualitative research with literature study which is using secondary data. A conclusion and results are the company need to build an awareness of the change in organization and follow the four tasks which are appreciating change, mobilizing support, executing change, and building change capability in order to make successful change. A company must know that every problem in organization can be solved just inside the organization not outside the organization so the leader needs to get information and data to know the problem that make this organization lagging behind from the competitor. After that the leader need to make a goal not too high and not too low so it will be easy to achieve that goal, and also understand evolution in business environment. Keywords: change management, steps of change, change process, type of change